1997
DOI: 10.1152/ajpcell.1997.273.2.c653
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-mediated phospholipid peroxidation assessed by gas chromatography-mass spectroscopy

Abstract: Disease pathophysiology frequently involves manifestations of the systemic inflammatory response syndrome. Oxyradicals represent key inflammatory mediators, and neutrophils are one important source of oxyradicals. This investigation examined neutrophil-mediated peroxidation of dilinoleoyl phosphatidyl-choline (DLPC) liposomes by monitoring the appearance of monohydroxyl linoleic acid with the use of gas chromatography-mass spectroscopy (GC-MS), compared with traditional assessment of thiobarbituric acid-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…We have observed that teprenone at a concentration of 10 to 100 m g / ml does not inhibit XO activity in gastric mucosal tissue preparations from compound 48 / 80-treated rats (unpublished data). Lipid peroxidation occurs via ROS generated not only by the xanthine-XO system but also by activated NADPH oxidoreductase in neutrophils (39,40). It is also known that MPO mediates lipid peroxidation in the presence of hydrogen peroxide with halide ions (41).…”
Section: Discussionmentioning
confidence: 99%
“…We have observed that teprenone at a concentration of 10 to 100 m g / ml does not inhibit XO activity in gastric mucosal tissue preparations from compound 48 / 80-treated rats (unpublished data). Lipid peroxidation occurs via ROS generated not only by the xanthine-XO system but also by activated NADPH oxidoreductase in neutrophils (39,40). It is also known that MPO mediates lipid peroxidation in the presence of hydrogen peroxide with halide ions (41).…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies indicate that aspirin can promote increase in neutrophil adhesion to venular endothelium in vivo [28]. In addition, it has been reported that neutrophils mediate lipid peroxidation through the production of superoxide anions by the activated NADPH oxidoreductase in the cells [29]. TBARS and tissues associated MPO activity were measured in gastric mucosa as indices of lipid peroxidation and neutrophil infiltration [30].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that activated neutrophils mediate lipid peroxidation via ROS generated by NADPH oxidoreductase. 42) It is also known that MPO mediates lipid peroxidation in the presence of H 2 O 2 with halide ions. 43) Therefore, a part of the aforementioned reduction of gastric mucosal TBARS content in C48/80-treated rats by vitamin E administration may be due to the inhibitory effect of the administered vitamin on neutrophil infiltration into gastric mucosal tissues.…”
Section: Discussionmentioning
confidence: 99%